2017
DOI: 10.18203/2320-6012.ijrms20172595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic supplement (kidilact) on prevention of acute diarrhea in children: a double-blind randomized clinical trial

Abstract: Background: Acute viral diarrhea is one of the most common diseases in children, which is associated with high risk of mortality. The present study aimed to determine the effect of Kidilact on the treatment of children with acute diarrhea.Methods: This double-blind randomized clinical trial was conducted on 84 children aged 6-60 months with diarrhea, hospitalized in pediatric ward of Amir al-Mu'minin hospital of Zabol, Iran. The patients who met the inclusion criteria were included and assigned to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Probiotics have been shown to improve acute gastroenteritis outcomes in children by reducing the severity of the conditions and improving recovery times [14,18,30]. Probiotics have also been shown to significantly reduce diarrheal symptoms associated with acute gastroenteritis [25,28,29,32].…”
Section: Gastrointestinal Benefits Of Probioticsmentioning
confidence: 99%
“…Probiotics have been shown to improve acute gastroenteritis outcomes in children by reducing the severity of the conditions and improving recovery times [14,18,30]. Probiotics have also been shown to significantly reduce diarrheal symptoms associated with acute gastroenteritis [25,28,29,32].…”
Section: Gastrointestinal Benefits Of Probioticsmentioning
confidence: 99%
“…In a randomised double-clinical trial in 2017, Hesaraki M et al (Hesaraki, 2017) investigated Kidilact's impact on diagnosis of children with severe diarrhoea. After 3 days in the experimental sample, the investigators observed that heart rate, body temperature as well as intestinal capacity decreased substantially (p<0,05).…”
Section: Literature Reviewmentioning
confidence: 99%